Utilization of Wheat with Enhanced Carotenoid Levels and Various Fat Sources in Hen Diets - Englmaierová, Michaela; Szmek, Jan; Skřivan, Miloš; Horčička, Pavel; Taubner, Tomáš; Skřivanová, Věra (Animals, 2025)
In this study, we evaluated the effects of two wheat varieties with different carotenoid concentrations (Pexeso and Tercie) and two fat sources with contrasting fatty acid profiles (rapeseed oil and lard) on hen performance, egg quality, and egg yolk retention of carotenoids. The feed conversion ratio of hens that received Tercie wheat and lard in their diet were greater than those of hens that received other diets (p = 0.002). Greater (p ˂ 0.001) eggshell thickness and strength occurred when hens were fed a Pexeso wheat diet. Moreover, Pexeso wheat and lard increased lutein (p ˂ 0.001 and p = 0.001) and zeaxanthin (p ˂ 0.001 and p = 0.001) contents in egg yolks. The highest lutein retention (p = 0.010) occurred in the groups that received Pexeso wheat (46.4 and 47.4%), and the highest zeaxanthin retention (p = 0.011) occurred with a Pexeso wheat and lard diet (59.5%). The lowest lutein and zeaxanthin retention occurred in hens fed a Tercie wheat and rapeseed oil diet (23.6% for lutein retention and 24.1% for zeaxanthin retention). The Pexeso wheat and rapeseed oil diet increased the concentrations of α- and γ-tocopherol (p ˂ 0.001 and p ˂ 0.001) in egg yolks, which influenced the oxidative stability of the eggs. Compared with other diets, a Tercie wheat and rapeseed oil diet led to the lowest oxidative stability in fresh eggs (p = 0.041). In conclusion, Pexeso wheat had greater retention of biologically active substances and higher mineral contents than Tercie wheat, which was reflected in the performance of hens and the quality of eggs. The combination of Pexeso wheat with rapeseed oil, which is rich in tocopherols and polyunsaturated fatty acids and has a favorable n-6/n-3 ratio, increased the tocopherol content and the oxidative stability of egg yolk fats.
Keywords: Pexeso wheat; tocopherols; zeaxanthin; fatty acids; lutein